Authentic Assessment as a Solution to Enhance Deep Learning and Maintain Academic Integrity in Higher Education - Cahyani, Vika Puji; Ahmad, Fandi; Soekarman, Soekarman; Nawi, Mohd Zulfakar Mohd (Journal of Educational Analytics, 2024)
Authentic assessment has become a major concern in higher education, especially in an effort to enhance deep learning and maintain academic integrity. This study aims to identify research trends related to authentic assessment and explain how authentic assessment design can promote deep learning while maintaining academic integrity in the digital era. This research uses a mixed method approach consisting of bibliometric analysis to identify research patterns related to the topic and narrative literature review to deeply analyse the themes and contributions of relevant research. The data that has been collected is then equipped with its attributes and analysed with VOSviewer software. The selected articles were then subjected to an in-depth analysis process on the content of the articles including the main theories used in authentic assessment, authentic assessment designs that support deep learning and the relationship between academic integrity. Based on the results of the study, it can be concluded that the research trends in the form of top 6 keywords related to authentic assessment are about authentic assessment (35), assessment (22), higher education (11), authenticity (6), academic integrity (5), assessment design (5), deep learning (4). This research offers practical recommendations for educators in designing authentic assessments that are relevant to the 21st century context.